Annual reports on NMR spectroscopy. - Webb, G. A. (Graham Alan), 1935- (Annual reports on NMR spectroscopy, 2002)
Nuclear magnetic resonance (NMR) is an analytical tool used by chemists and physicists to study the structure and dynamics of molecules. In recent years, no other technique has grown to such importance as NMR spectroscopy. It is used in all branches of science where precise structural determination is required and where the nature of interactions and reactions in solution is being studied. Annual Reports on NMR Spectroscopy has established itself as a means for the specialist and nonspecialist alike to become familiar with new applications of NMR spectroscopy in all branches of chemistry. As with other members of this series, Volume 45 consists of a collection of accounts of progress in various areas of NMR activity. The first report covers Temperature Measurements using NMR, following this is a review on Structural Studies of Amino Acids, Polypeptides and Proteins in the Solid State. The next contribution is on STRAFI and SPI Magnetic Resonance Imaging. The final contribution is a report on NMR Studies of Internal Hydrogen Bonds in Metalloproteins. - Temperature Measurements using NMR - Structural Studies of Amino Acids, Polypeptides and Proteins, in the Solid State by 1H CRAMPS NMR - Stray Field (STRAFI) and Single Point (SPI) Magnetic Resonance Imaging - NMR Studies of Internal Hydrogen Bonds in Metalloproteins.